(untitled) (Global Journal of Science Frontier Research, 2014)
We propose a method of obtaining the moment of some continuous bi-variate distributions with parameters 1 1 2 2 , , and considered are non-negative real numbers that need not be integers. The results obtained using ( , ) n g c d are the same as results obtained using other methods such as moment generating functions when they exist.